THE EFFECT OF DIRECTED READING THINKING ACTIVITY STRATEGY TOWARD INTENSIVE READING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Dolandari Misvaindra; Elfia Sukma (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low ability of intensive reading of elementary school students because the implementation of intensive reading has not met the nature of intensive reading itself. The purpose of this study was to determine the effect of DRTA strategies on the intensive reading skills of elementary school students. This research was experimental in the form of a pre-test-post-test control group design. The results found that the testing of intensive reading skills in the control class and the experimental class in the pre-test was t count < t table, 0.796 < 0.281, so there was no difference in intensive reading skills in the control class and the experimental class in the pre-test which meant that there is no difference in the initial ability of students before being given action. The result showed that intensive reading skills in the control class and experimental class at the time of the post-test was t count > t table or 6.391> 2.642 so that there was a significant difference in the intensive reading ability of elementary school students between the control class and the experiment at the post-test. It was concluded that there was an influence of Directed, Reading, Thinking, Activity (DRTA) strategy on the intensive reading skills of elementary school students. The implication of this study is as teacher reference for improving the intensive reading skills of elementary school student.